Determinan Praktik Kebersihan Menstruasi Santriwati Pondok Pesantren di Sulawesi Selatan - Bahtiar, Harismawati; Nasir, Narila Mutia (Journal of Religion and Public Health, 2023)
AbstractPoor menstrual hygiene practices may have impact on women's reproductive health. In addition, it also can influence on study performance and social activities for female adolescent. Islamic boarding schools are formal educational institutions that have different vulnerabilities from other educational institutions due to similar accessibility to sanitation and having limited source of information. This study aimed to know the determinants of the menstrual hygiene practices among female students in the Al-Ikhlas Islamic Boarding School (Pesantren) Ujung Bone, South Sulawesi. This was a quantitative research using a cross-sectional study design. Chi-square test was performed for the statistical test. Of 120 female students were participated in this study by filling in the structured questionnaire through Google form. The results of this study indicated that 50% respondents had poor menstrual hygiene practice. Furthermore, this study found four variables that were statistically significant related to menstrual hygiene practices of female students at the Al-Ikhlas Ujung Bone Islamic Boarding School, including knowledge (p value = 0.005), attitude (p value = 0.001), age of menarche (p value = 0.033), and belief (p value = 0.040). To improve the menstrual hygiene practices, the Islamic Boarding Schools can include materials about reproductive health and menstrual hygiene in learning activities and encourage the utilization of health media as a source of information. The further study may analyze socio economics determinant and peer influence on menstrual hygiene practices comprehensively.Keywords: Menstrual Hygiene, Islamic Boarding School, Female Students